High-fat diet stimulated butyric acid metabolism dysbiosis, altered microbiota, and aggravated inflammatory response in collagen-induced arthritis rats - Yantong Liu; Yang Zhang; Jie Zhang; Shuang Ren; Qi Cao; Hongxi Kong; Qiangqiang Xu; Ruoshi Liu (Nutrition & Metabolism)
Abstract Background Research has demonstrated that obesity may be associated with rheumatoid arthritis (RA). In addition, Dysbiosis of intestinal microbiota and their metabolites has been linked to the occurrence and development of RA and obesity. However, the mechanism by which obesity affects RA remains unclear.In this study, we explored the impact of high fat diet(HFD) on collagen-induced arthritis (CIA) rats and revealed its mechanisms based on gut microbiota and metabolomics. Methods Based on diet and modeling, rats were divided into normal group (Con), CIA model group, HFD group (HFD), and HFD + CIA group (HCIA). The effect of HFD on arthritis in CIA rats were investigated based on the arthritis index (AI), weight, blood lipid levels, and inflammatory cytokines. Moreover, HE staining and micro-CT were performed to evaluated the effect of HFD on the pathology of joints and synovial tissues in CIA rats.16S rRNA amplicon sequencing and liquid chromatography-mass spectrometry (LC–MS) were employed to explore changes in gut microbiota and short-chain fatty acids (SCFAs). Results The AI scores, inflammatory cytokines and bone destruction parameters in the HCIA group were significantly higher than those in the other three groups. The results of 16S rRNA amplicon sequencing and metabolomics showed that compared with the other three groups, the expression of g_Muribaculaceae and butyric acid were reduced in the HCIA group. Spearman and linear correlation analyses revealed a positive correlation between g_Muribaculaceae abundance and butyric acid levels. Conclusions HFD stimulated butyric acid metabolism dysbiosis, altered microbiota, and aggravated inflammatory response in CIA rats.